Asymmetric Hydrocarboxylation of Olefines by Chiral Palladium Complexes - Carlo Botteghi; Giambattista Consiglio; Piero Pino (CHIMIA)
Asymmetric induction up to 14% have been obtained in the hydrocarboxylation of olefinic hydrocarbons with carbon monoxide and alcohols in the presence of PdCl2 and (–)-DIOP (= 2,3-O-isopropylidene-2,3-dihydroxy-1,4- bis(diphenylphosphino)butane).